EPIDEMIOLOGY, CLINICAL COURSE, TREATMENT AND PREVENTION OF MEASLES (Journal of Science-Innovative Research in Uzbekistan, 2024)
Measles is an acute infectious disease caused by the measles virus, which infects the epithelium of the upper respiratory tract and skin. Clinically characterized by a severe syndrome of general infectious intoxication, pathognomonic enanthema, maculopapular rash, conjunctivitis and respiratory tract (respiratory) syndrome. The syndromic disease was described in 1890 by Dr. Belsky (Pskov), in 1895 by pediatric doctor Filatov, and in 1898 by Dr. Koplik (USA).